Response Assessment Following Image-Guided Therapy of Hepatocellular Carcinoma - Pankaj Gupta; Naveen Kalra; Ajay Gulati; Vishnu Dev; Ujjwal Gorsi; Sreedhara B. Cheluvashetty; Praveen Kumar-M; Ajay Duseja; Virendra Singh; Radha K. Dhiman; Manavjit Singh Sandhu (Journal of Clinical Interventional Radiology ISVIR)
Image-guided locoregional therapies have an important role in the management of patients with hepatocellular carcinoma (HCC). Recent advances in the ablative as well as endovascular therapies have expanded the role of interventional radiologists in the treatment of HCC. Following image-guided therapy, an accurate response assessment is vital. Knowledge regarding normal postprocedure changes and subtle signs of residual or recurrent disease is important. In this review, we discuss various response evaluation criteria currently employed for HCC. We also discuss the postprocedure imaging features suggestive of residual disease or recurrence and imaging biomarkers for response assessment.